(untitled) (Patan Prospective Journal, 2024)
This study evaluates the efficacy of the Weibull, lognormal, and gamma distributions in modeling PM2.5 and TSP concentrations in urban Kathmandu, specifically at Pulchok and Ratnapark, based on data collected from May 1, 2024 to October 31, 2024. The analysis revealed notable disparities in pollution levels, with Pulchok exhibiting higher and more fluctuating concentrations compared to Ratnapark. Both the Weibull and lognormal distributions demonstrated superior fit for the PM2.5 and TSP data, as confirmed by the Kolmogorov-Smirnov test. These decisions highlight the significant influence of urban pollution sources and highly the importance of robust statistical modeling in air quality management and health risk assessment.